In Vitro Culture of Phalaenopsis amabilis (L.) Blume Orchid for Seedling Production with Banana Extract Supplementation and Light Treatment for Ex Situ Conservation - Dyah Ayu Puspita Arum; Endang Semiarti (Universitas Gadjah Mada, 2022)
In vitro culture is one of the effective cultivation methods for seedling production of orchids that can be used as a powerful tool in the conversation of orchids. The aims of the present study were to (i) investigate the effects of the addition of banana extract (0 g/l, 100 g/l, and 150 g/l) on media (NP media), in two different light regimes (light and dark conditions) on the growth of plantlets of an epiphytic orchid Phalaenopsis amabilis in in vitro culture. Methods used included (i) subculturing orchid seedlings in treatments media, (ii) measuring leaves and roots chlorophyll content and growth parameters, (iii) anatomical preparation of leaves and roots of the seedlings. The results showed that the best condition for getting greater seedlings of P. amabilis plantlets is in media with an addition of 100 g/L banana extract in light condition. The highest amount of chlorophyll in the P. amabilis leaves was found in medium with the addition of 100 g/L banana extract medium in light conditions. The thickness of mesophyll and the largest root diameter of P. amabilis seedlings were also found in media with the addition of 100 g/L banana extract medium in light condition. In conclusion, the addition of 100gr/L banana extract into basic culture medium will be beneficial for seedlings production of P. amabilis with great appearance, for ex situ orchid conservation programs.